THE INFLUENCE OF GEOMETRICAL SIZES OF FIBRES ON ACOUSTIC EMISSION AT DESTRUCTION OF COMPOSITION MATERIAL - Філоненко, С.Ф.; Космач, О.П. (Science-based technologies, 2009)
The modeling of composite material fracture and formed of acoustic emission signal is conducted depending onthe geometrical size of fibers. Basic conformities to the law of change acoustic emission signal parameters areshowed.